2020
DOI: 10.3892/mco.2020.2119
|View full text |Cite
|
Sign up to set email alerts
|

A case of Stewart‑Treves syndrome occurring in the abdominal wall successfully treated with eribulin: A case report

Abstract: Angiosarcoma (AS) is a rare and aggressive tumor with high rates of local recurrence and distant metastasis. Stewart-Treves syndrome (STS) is defined as AS arising in the setting of chronic lymphedema, and is extremely uncommon in the lower abdominal wall. Eribulin mesylate (eribulin) is a non-taxane microtubule inhibitor that has been approved in Japan for treating soft tissue sarcoma. The current study reports the case of a 76 year-old woman with STS in the lower abdominal wall who exhibited an excellent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Some studies have reported that microsurgery, immunotherapy, and drugs may be effective in STS treatment, but most treatment schemes still emphasize the importance of radical surgery in determining the survival rate of patients. 17 , 18 , 19 In a study conducted in Canada, the average age of the patients was 61.2 years, and the average time from lymphedema to malignancy was 15.8 years. A total of 69.8% of the patients had a history of malignancy, and 53.7% had a history of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that microsurgery, immunotherapy, and drugs may be effective in STS treatment, but most treatment schemes still emphasize the importance of radical surgery in determining the survival rate of patients. 17 , 18 , 19 In a study conducted in Canada, the average age of the patients was 61.2 years, and the average time from lymphedema to malignancy was 15.8 years. A total of 69.8% of the patients had a history of malignancy, and 53.7% had a history of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…209 The next four examples describing promising response in cASs appeared in 2018 [214][215][216] with one surprisingly successful outcome of chronic lymphoedema induced AS of the abdominal wall. 217 Less optimistic were the results for a case of intimal AS from the common iliac artery, where ERB treatment did not prevent tumour progression. 218 Currently ongoing phase II clinical trial aimed to asses safety and effectiveness of ERB in AS and epithelioid hemangioendothelioma treatment is recruiting.…”
Section: A Microtubule-targeting Agent Eribulin Mesylate (Erb)mentioning
confidence: 99%
“…At first, metastatic cardiac AS has been successfully controlled with ERB implemented as the eighth line of treatment 209 . The next four examples describing promising response in cASs appeared in 2018 214–216 with one surprisingly successful outcome of chronic lymphoedema induced AS of the abdominal wall 217 . Less optimistic were the results for a case of intimal AS from the common iliac artery, where ERB treatment did not prevent tumour progression 218 .…”
Section: Other Molecular Possibilities and Immunotherapymentioning
confidence: 99%
“…Classical mono-or combined chemotherapies are those usually applied in sarcomas: anthracyclines, paclitaxel, dacarbazine, bleomycin, and actinomycin D [4,5]. Eribulin has recently demonstrated some activity even in second-line treatment [8]. In selected cases, hyperthermic isolated limb perfusion with TNF-alpha/melphalan or mitoxantrone/paclitaxel combinations have been tried with some results [9,10].…”
Section: Standard Treatmentmentioning
confidence: 99%